Penataan Pedestrian pada Kawasan Kampus 1, Universitas Muhammadiyah Bengkulu - Geby Fatona; Rizqiyah Safitri Juwito; Mariska Pratimi; Anggi Yudha Pratama; Renitha Sari; Pretty Maggiesty Rosantika (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study aims to analyze and provide recommendations regarding the arrangement of pedestrian facilities in the Campus 1 area of Muhammadiyah University of Bengkulu. This area plays an important role as the center of academic, social, and mobility activities of the academic community, which heavily depends on pedestrian facilities. Field observations reveal several key issues with the pedestrian facilities in this area, including the sidewalk width not meeting the minimum standard, lack of accessibility features for people with disabilities, absence of vegetation or shade, and insufficient signage and road markings to guide users. These conditions result in discomfort and insecurity for pedestrians, as well as failing to support the principles of inclusivity in infrastructure planning. The research employs a descriptive qualitative and quantitative approach with a case study method. Data were collected through field observations, questionnaires, interviews, and literature reviews. Based on the analysis, the majority of respondents expressed the need for improvements to the sidewalk quality, addition of shade trees, enhanced accessibility for people with disabilities, and the installation of supporting facilities such as street lighting. The study then recommends several improvement measures, such as widening the sidewalks to at least 1.5 meters, providing ramps and Guiding blocks, planting vegetation along the pedestrian routes, and installing road signs and markings. These recommendations aim to improve pedestrian comfort and safety. It is hoped that the results of this study can serve as a reference for Muhammadiyah University of Bengkulu in creating a campus area that is more friendly, safe, comfortable, and inclusive for all users, while also supporting sustainable mobility.